Do Multi-Sector Bond Funds Pose Risks to Emerging Markets? - Cortes, Fabio (IMF Working Papers; Working Paper ;, 2020)
Emerging economies in the post-crisis period increasingly saw portfolio debt inflows from a type of large international investment fund: Multi-Sector Bond Funds (MSBFs). These investors have lacked adequate representation in the literature. This paper constructs a new detailed database from micro-level MSBF emerging market (EM) holdings from 2009:Q4-2018:Q2. Exploiting this data, the paper assesses the risks they pose to the financial stability of specific emerging bond markets. The data shows that MSBFs are highly concentrated-both in their positions and their decision-making. The empirical results further suggest that MSBFs exhibit opportunistic behavior (and more so than other investment funds). In periods of high risk aversion, large MSBF portfolio reallocations out of EMs can be associated with underperformance of the same markets, signaling the importance of monitoring their footprint and better understanding their asset allocation decisions.